Piezoelectric characteristics of CMOS compatible AIN SAW resonators - Md Ralib @ Md Raghib, Aliza 'Aini; Pandian, Mohanraj Saundara; Ferrer, Eloi Mariago; Song, Charlie TayWee; Shunmugam, Muniandy; Zainuddin, Ahmad Anwar; Nordin, Anis Nurashikin (2014)
In this work, we predict the surface acoustic wave characteristics by 2D COMSOL finite element modeling. The dispersion of simulated acoustic mode shapes, acoustic phase velocity and coupling coefficient were performed on a CMOS-compatible 1.4 GHz SAW resonator. C-axis oriented Aluminium Nitride (AIN) was chosen as the piezoelectric material due to its compatibility with CMOS technology and higher phase velocity. The influences of AIN thickness on electromechanical coupling coefficient and phase velocity are discussed. High acoustic velocities (v∼5220 m/s) and coupling factors (k2∼0.19%) can be observed for SAW resonator with khAIN∼ 3.9. The measurement results are found to be consistent with FEM results with deviation less than 6% for resonance frequency and phase velocity.